2013
DOI: 10.1016/j.clinbiomech.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of step length, age, and fall history on hip and knee kinetics and knee co-contraction during the maximum step length test

Abstract: Background-Maximum step length is a brief clinical test involving stepping out and back as far as possible with the arms folded across the chest. This test has been shown to predict fall risk, but the biomechanics of this test are not fully understood. Knee and hip kinetics (moments and powers) are greater for longer steps and for younger subjects, but younger subjects also step farther.Methods-To separate effects of step length, age, and fall history on joint kinetics; 14 healthy younger, 14 older non-fallers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In older adults, this stepping capacity is frequently reduced: their reactive steps are shorter ( Luchies et al, 1994 ) and they tend to collide the swing foot with the stance leg ( Maki et al, 2000 ). Moreover, in fallers, the maximum step length ( Cho et al, 2004 ; Schulz et al, 2013 ) and volitional stepping speed ( Melzer et al, 2007 ) is reduced compared to non-fallers. As a result, if stepping capacity is decreased, the risk for falls increases ( Okubo et al, 2017 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In older adults, this stepping capacity is frequently reduced: their reactive steps are shorter ( Luchies et al, 1994 ) and they tend to collide the swing foot with the stance leg ( Maki et al, 2000 ). Moreover, in fallers, the maximum step length ( Cho et al, 2004 ; Schulz et al, 2013 ) and volitional stepping speed ( Melzer et al, 2007 ) is reduced compared to non-fallers. As a result, if stepping capacity is decreased, the risk for falls increases ( Okubo et al, 2017 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our ndings differ from a prior study that reported no differences in postural sway timing or amplitude between fallers and non-fallers following lateral shoulder-impact perturbations, 18 suggesting that different body segment perturbations may elicit distinct reactive balance control strategies. Additionally, while previous research linked greater cocontraction to more joint stability and poorer balance control, 42,43 this study has observed that older fallers even with poorer balance performance than non-fallers (lower Mini-BEST scores) were able to reduce agonist-antagonist co-contractions of lower-limb muscles and achieve larger knee/hip exion for a suspensory strategy. On top of them, this study has observed fallers with the longer activation durations of ankle dorsi exor and hip abductor together with the longer ankle dorsi exion duration than non-fallers, which may be necessary for maintaining a knee bending posture during the suspensory strategy.…”
Section: Fallers Tended To Use Suspensory Strategies Following Unexpe...mentioning
confidence: 58%
“…Thus researchers have used the Maximum Step Length (MSL) test which assesses both dynamic balance and leg strength. Clinically, a decrease in the MSL test is associated with an increase decade of life and performance on clinical assessments that are used to predict falls; as MSL decrease, fall risk increases (Cho et al, 2004;Lindermann et al, 2003;Schulz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%